Sistem Pakar Diagnosa Penyakit Padi Menggunakan Metode Certainty Factor - Dewi Mugniati; Arita Witanti (STMIK Budi Darma, 2024)
The role of rice in Indonesia is as the main food ingredient that is irreplaceable because Indonesians make rice their staple food. Many people in Indonesia work as farmers and NTB province is one of the provinces where most people work as farmers. Rice planted by the community is not free from disease because disease can attack from anywhere. Diseases that attack rice plants often make farmers confused about how to handle them, especially for farmers who have minimal knowledge about diseases that can attack rice and their solutions. Due to the lack of time and knowledge, when rice fields are affected by disease, many people will discuss with experts. However, due to the lack of time, people are reluctant to go all the way to find experts. Therefore, an expert system was created that is used to detect symptoms and types of diseases that attack rice plants that can be used anywhere and anytime because this expert system is web-based. Based on expert system research on 30 farmers who use the certainty factor method as a basis for calculation can produce similarity of answers with experts by 96%.